Muskox Bull Killed by a Barren-Ground Grizzly Bear, Thelon Game Sanctuary, N.W.T. - Gunn, Anne; Miller, Frank L. (ARCTIC, 1982)
The carcass of an adult muskox bull (Ovibos moschatus) killed by a barren-ground grizzly bear (Ursus arctos richardsoni) was found in the Thelon Game Sanctuary. It is suggested that adult muskox bulls along the Thelon River system have become prey for at least some grizzly bears that have learned to ambush them in dense vegetation.Key words: muskoxen (Ovibos moschatus); grizzly bear (Ursus arctos richardsoni); predation Mots clés: boeuf musque (ovibos moschatus); ours brun "de la toundra" (Ursus arctos richardsoni); prédateurs